DEVELOPMENT OF GUIDANCE AND COUNSELING METHODS IN IMPROVING SELF-MANAGEMENT OF EPILEPSY PATIENTS IN THE NEUROLOGY CLINIC OF KANJURUHAN KEPANJEN GENERAL HOSPITAL - Arsa, Sandi Alfa Wiga; Sulistya, Denok Panglipuring (Jurnal Surya, 2021)
Background: Epilepsy is the oldest neurological disease, found at all ages, can cause disability and mortality. Epilepsy has a higher risk of death due to seizures. Knowing the trigger seizures and taking steps to manage the disease greatly helps reduce the occurrence of death. Purpose: this study was to investigate the effect of the health education Guidance and Counseling Method on increasing self-management in epilepsy patients in the Neurology Clinic in Kanjuruhan Kepanjen Hospital. Methods: This research is a pre-experimental design with a one-group pre-post test village approach. The population was 44 respondents, 40 respondents samples, purposive sampling technique, data collection using a questionnaire, and data analysis using statistical test Wilcoxon Signed Rank test. Results: Wilcoxon Signed-Rank Test results obtained 0.000 (Î± â‰¤ 0,05) resulted in the influence of health education guidance and counseling method to the increase of self-management in epilepsy patients at Kanjuruhan Kepanjen Neurology Clinic. Conclusion: Based on the results of this study it was important for health workers to improve knowledge and skills in health education, especially guidance and counseling methods to support the recovery of epilepsy patients by increasing self-management of epilepsy patients.